2019
DOI: 10.3390/jfb10020023
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly pH-Sensitive Hybrid Membranes by Simultaneous Electrospinning of Amphiphilic Nanofibers Reinforced with Graphene Oxide

Abstract: Nanofibrous-based pH sensors have shown promise in a wide range of industrial and medical applications due to their fast response time and good mechanical properties. In the present study, we fabricated pH-sensitive sensors of nanofibrous membranes by electrospinning polyurethane (PU)/poly 2-acrylamido-2-methylpropanesulfonic acid (PAMPS)/graphene oxide (GO) with indicator dyes. The morphology of the electrospun nanofibers was examined using scanning electron microscopy (SEM). The effect of hydrophilic polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The inclusion of GO into an electrospun material for use in medical devices and biomaterials can improve its hydrophilicity due to the existence of oxygen-abundant functional groups on the nanomaterial. , It is also widely reported that GO improves mechanical features such as tensile strength, ductility, electroconductivity, etc. when included in an electrospun matrix. ,, While we understand that the use of GO in small concentrations in areas such as tissue engineering, drug delivery, wound healing, etc.…”
Section: Biomaterials/medical Devicesmentioning
confidence: 99%
“…The inclusion of GO into an electrospun material for use in medical devices and biomaterials can improve its hydrophilicity due to the existence of oxygen-abundant functional groups on the nanomaterial. , It is also widely reported that GO improves mechanical features such as tensile strength, ductility, electroconductivity, etc. when included in an electrospun matrix. ,, While we understand that the use of GO in small concentrations in areas such as tissue engineering, drug delivery, wound healing, etc.…”
Section: Biomaterials/medical Devicesmentioning
confidence: 99%
“…In this section, we systematically classify the sensing objects of biochemical sensors into gas and liquid categories. Among them, gases include gas molecules, water molecules, and volatile substances, while liquids mainly include carbohydrates, biomacromolecules, aqueous ions, and other clinically relevant analytes [48][49][50][51][52]. In the following content, we will introduce the latest research progress of graphene-fiber sensors, including different sensing structures and sensing targets, and analyze their sensing performances.…”
Section: Graphene-fiber Biochemical Sensing Implementations and Applicationsmentioning
confidence: 99%
“…Dispersion GNMs into polymer matrices have been reported to improve the electrical, mechanical, thermal properties and other properties of polyslfones [186,187], polyimide [188,189], polycarbonates [190,191], polyamides [192,193], polyethylene terephthalate [192,193] and polybutylene terephthalate [194,195]. Gorji et al [196] reported that the incorporation of GO into electrospun of PU and pH-sensitive dyes contributed to a faster response (7 s) and improved the sensor's sensitivity to detect pH in chemical vapor solution. Table 3 summarizes the recent studies on impregnating GNMs into ESNFs and the subsequent improved properties.…”
Section: Properties Of Electrospun Gnms Nanocompositesmentioning
confidence: 99%